The Illusion of Control: User Perceptions of Privacy and Data Agency on Social Media Platforms After GDPR - Kabelo Dube; Kgomotso Seretse; Keaolwe Matlhomola (Journal of Social Science Utilizing Technology, 2026)
Background. The General Data Protection Regulation (GDPR), implemented in 2018, aimed to enhance user privacy and give individuals more control over their personal data on social media platforms. However, despite these regulatory changes, concerns about data privacy and user agency persist. This study explores how users perceive their privacy and data control on social media platforms post-GDPR, focusing on whether the regulation has led to a genuine increase in user agency or if it remains an illusion. Purpose. The research aims to assess the gap between perceived and actual control over personal data, as well as the factors that influence these perceptions. Method. Using a mixed-methods approach, the study combines surveys and in-depth interviews with social media users across various platforms. Results. The findings reveal that while users feel more empowered by the GDPR’s transparency requirements, many still feel limited in their ability to effectively control their data. Privacy settings remain confusing, and the complexity of consent mechanisms leaves users uncertain about the full extent of their data usage. Conclusion. The study concludes that, while GDPR has improved transparency, it has not fully addressed the underlying issues of user agency, suggesting the need for further regulatory refinement to provide users with meaningful control over their data.